Participatory management of weed infestation in Lake Tana - setting a better future in the front mirror - Sewunet, Birhanu; Girma, Haileyesus; Debela, Sisay Abebe; Luke, Amana Ogeto; Gebrehiwot, Mesfin (Frontiers in Ecology and Evolution, 2022)
Lake Tana is one of the biosphere reserves in Ethiopia registered by the United Nations Educational, Scientific, and Cultural Organization (UNESCO). Water hyacinth is expanding in the lake owing to increased nutrient load from the watershed. As efforts from the government alone could not bring the anticipated change, local peoples’ engagement and contribution are believed to sustainably and effectively manage the watershed and prevent the weed’s spreading. This study, therefore, aims to estimate households’ contribution (willingness to pay–WTP–and willingness to contribute labor–WTCL–) to prevent and control water hyacinth and hence improve lake ecosystem services through a hypothetical watershed management in Lake Tana. This study applied quantitative and qualitative methods. It was conducted among 560 randomly selected households of the Libo-kemkem district using a contingent valuation method from March to April/2021. Eleven key informant interviews were also conducted. Bivariable and multivariable interval regression models were used to identify the determinants of households’ potential contribution. Thematic analysis was used to analyze the qualitative data. As the weed is believed negatively impact the ecosystem services provided by the lake, 72% of the respondents showed willingness to contribute to the proposed management program. About 32 and 39% of the respondents were willing to pay in cash and to contribute labor, respectively, to prevent weed infestation. On the other hand, 28% of them were neither willing to contribute in cash nor in labor to the hypothetical market. The findings showed respondents’ mean annual WTP and WTCL were 632.8 Ethiopian birr and 30.1 man-days per household, respectively. The place of residence, educational status, farm plot area, household income, family size, and conference participation significantly influenced WTP and/or WTCL. In this hypothetical improvement scenario, an estimated annual WTP and WTCL of nearly 12 million Ethiopian birr and 700 man-days per year, respectively, are reported considering the total households in the study area. Therefore, collaborative efforts by different stakeholders are the next steps to realize the hypothetical contributions.